KEPUTUSAN TETAP BERTAHAN SETELAH PANDEMI COVID 19: AKSESBILITAS KESELAMATAN & KESEHATAN KERJA PADA INDUSTRI KECIL PENGOLAHAN KAYU - Kristina, Anita; Jumali, Muhamad Abdul (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
Institutional rules, values ​​and beliefs help support the resolution of industrial conflicts. The conflict arises due to the internal environmental conditions provided by the industry owner. This study discusses the case of work safety during the covid 19 pandemic, namely in the small wood craft industry in Bojonegoro. The analytical method uses a qualitative approach (industrial institutional analysis), using FGD as a tool for data analysis and validation. The results show that the pattern of small wood craft industry has traditional institutions that support the accessibility of occupational safety and health. The ability to survive arises as a result of the owner's and workers' compliance initiatives towards work safety. The value built on occupational safety in small industries also adapts to their traditional institutions to meet the challenges of conflicting health decent work fulfillment. This study concludes that industrial accessibility on occupational safety and health issues has examined the capacity of traditional institutions in the form of agreements that require adaptation of traditional values ​​(trust and brotherhood).